2022
DOI: 10.21873/cdp.10074
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the Prognostic Nutritional Index in Neoadjuvant Chemoradiotherapy for Rectal Cancer

Abstract: Background/Aim: Prognostic nutritional index (PNI) and neutrophil-to-lymphocyte ratio (NLR) indicate nutritional status and host immunity. We used immunohistochemistry and apparent diffusion coefficient (ADC) values calculated using diffusion-weighted imaging (DWI) to investigate relationships of these factors with pathological and radiological characteristics in rectal cancer treated with neoadjuvant chemoradiotherapy (nCRT). Patients and Methods: We evaluated expression levels of VEGFA, CD8, CD33, and ADC va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
2
1
0
Order By: Relevance
“…Likewise, lymphocytes are involved in anti‐tumoral immunity, and lymphocyte dysfunction or imbalance is associated with cancer progression 28 . Previous studies have shown that pretreatment PNI predicted the outcome in patients with CRC, 29,30 and our results further validated the prognostic value of PNI in patients with BM from CRC. Overall, both malnutrition and immune dysfunction represent unfavorable conditions in the prognosis of patients with cancer.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Likewise, lymphocytes are involved in anti‐tumoral immunity, and lymphocyte dysfunction or imbalance is associated with cancer progression 28 . Previous studies have shown that pretreatment PNI predicted the outcome in patients with CRC, 29,30 and our results further validated the prognostic value of PNI in patients with BM from CRC. Overall, both malnutrition and immune dysfunction represent unfavorable conditions in the prognosis of patients with cancer.…”
Section: Discussionsupporting
confidence: 77%
“…[25][26][27] Likewise, lymphocytes are involved in anti-tumoral immunity, and lymphocyte dysfunction or imbalance is associated with cancer progression. 28 Previous studies have shown that pretreatment PNI predicted the outcome in patients with CRC, 29,30 Besides the comorbidity indices, our analyses also revealed that the control of the primary CRC and the presence of multiple BM were independent factors that predicted survival. The impact of coexisting extracranial metastases (ECM) and the number of BM at the time of the diagnosis of BM have been reported and were…”
Section: Discussionsupporting
confidence: 50%
“…Currently, several studies have utilized inflammatory indexes or circulating lymphocyte subsets to predict treatment response in rectal cancers. 24 , 25 , 26 , 27 , 28 , 29 To our knowledge, so far, no study has reported the evaluation of the efficacy of NCRT for rectal MACs using the combination of inflammatory indexes and circulating lymphocyte subsets. In this study, we developed an XGB model based on preoperative clinicopathological parameters, inflammatory indexes, and the circulating lymphocyte subsets to predict treatment response to NCRT in rectal MAC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several studies have utilized inflammatory indexes or circulating lymphocyte subsets to predict treatment response in rectal cancers 24–29 . To our knowledge, so far, no study has reported the evaluation of the efficacy of NCRT for rectal MACs using the combination of inflammatory indexes and circulating lymphocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, other studies have shown a decrease in PNI levels post-CRT compared with pre-CRT in patients with rectal cancer. They also mentioned that the pre-CRT PNI had an impact on overall survival and disease-free survival [ 15 ]. Okugawa et al [ 16 ] did not find a significant correlation between the pre-CRT PNI and adverse CRT effects, but a low pre-CRT PNI was an independent risk factor for the ineffectiveness of CRT.…”
Section: Discussionmentioning
confidence: 99%